Biodiesel production catalysed by low-cost liquid enzyme Eversa® Transform 2.0: Effect of free fatty acid content on lipase methanol tolerance and kinetic model. (1st January 2021) - Chang, Mun Yuen; Chan, Eng-Seng; Song, Cher Pin
Graphical abstract: Highlights: Liquid lipase from genetically modified Aspergillus oryzae was used to catalyse biodiesel production. Initial FFA content in feedstock was varied to represent low-quality feedstock. Highest biodiesel conversion of 96.7% was obtained using feedstock with 80% FFA content. Methanol tolerance of liquid lipase was improved in the presence of FFA. Modified kinetic model was used to estimate the reaction rates of feedstocks with varying FFA content. Abstract: A low-cost liquid lipase from genetically modified Aspergillus oryzae (Eversa® Transform 2.0) was used in this study for biodiesel production. The catalytic performance of this enzyme was evaluated using refined palm oil adjusted with different free fatty acid (FFA) content. The methanol-to-oil molar ratio was varied from 1:1 to 8:1 to determine the reaction rate, ester conversion and methanol tolerance of this enzyme at different FFA content. The reaction was carried out at low temperature (40 °C) for 24 h using very low enzyme concentration (0.2 wt%). The results showed that the enzyme could tolerate a higher dosage of methanol and could increase reaction rate and conversion when higher FFA content was present in the feedstocks. A biodiesel conversion of 97% could be obtained when the feedstocks contained ≥80 wt% FFA. Furthermore, a new semi-empirical model based on the Ping-Pong Bi-Bi mechanism has been developed to estimate the reaction kinetics of biodiesel production from feedstocks containing a mixture of triacylglycerol and FFA. In conclusion, Eversa® Transform 2.0 can be used for the production of biodiesel from low-quality feedstocks containing high FFA content in a sustainable and economical manner.